2020
DOI: 10.21037/atm-20-2045a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous and inhalation anesthesia on blood glucose and complications in patients with type 2 diabetes mellitus: study protocol for a randomized controlled trial

Abstract: Background: Diabetes mellitus (DM) is a metabolic disorder syndrome caused by relative or absolute lack of insulin and varying degrees of insulin resistance. The type and regimen of anesthesia may affect perioperative hyperglycemia following major surgical stress. The effect of perioperative anesthetics on the blood glucose level of diabetic patients will play an essential role in the postoperative recovery of patients.However, there is no rigorously-designed randomized controlled trial to compare the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…Secondly, the reported effect could be attributed to an agonizing effect of midazolam on GABA receptors on insulin resistance, which is coincident with type-2 diabetes mellitus [7] , in support of this attribution, Li et al, [23] using type-2 DM animal model found supplementation by GABA-rich yogurt favorably regulated homeostasis model assessment of β -cell function, improved islet cells morphology and lowered total cholesterol in a dosedependent manner. Thereafter, Rezazadeh et al, [24] using animal model of type-2 DM found GABA therapy improved insulin resistance in diabetic animals by increasing the expression of GLUT4, the main glucose transporter to the cell, whereby glucose is metabolized with subsequent decrease of BGC.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Secondly, the reported effect could be attributed to an agonizing effect of midazolam on GABA receptors on insulin resistance, which is coincident with type-2 diabetes mellitus [7] , in support of this attribution, Li et al, [23] using type-2 DM animal model found supplementation by GABA-rich yogurt favorably regulated homeostasis model assessment of β -cell function, improved islet cells morphology and lowered total cholesterol in a dosedependent manner. Thereafter, Rezazadeh et al, [24] using animal model of type-2 DM found GABA therapy improved insulin resistance in diabetic animals by increasing the expression of GLUT4, the main glucose transporter to the cell, whereby glucose is metabolized with subsequent decrease of BGC.…”
Section: Discussionmentioning
confidence: 88%
“…Anesthesia and surgery can aggravate diabetic patient and increase the incidence of complications secondary to poor blood glucose control, so decreasing glucose variability during admission for surgery is essential to reduce re-admission rates and length of stay of T2D patients [7] . The type and regimen of anesthesia may affect perioperative hyperglycemia following major surgical stress [8,9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…На данный момент проводится два больших проспективных клинических исследования, изучающих влияние различных типов анестезии на уровень гликемии в периоперационном периоде у пациентов с СД. Мы надеемся, что данные исследования помогут «расставить все точки над i» в данной проблеме [79,80]. В нескольких клинических исследованиях предпринимались попытки оценить влияние региональной анестезии на развитие гипергликемии в периоперационном периоде.…”
Section: влияние различных видов анестезии на уровень глюкозы плазмы ...unclassified
“…It has also been commonly noted that binge drinking and psychiatric illnesses are linked to diabetes ( Munukutla et al, 2016 , Kessler et al, 1997 ). Previous research has demonstrated that the kind and length of anaesthesia have an impact on systemic perioperative hyperglycemia after surgical stress, as well as play a role in post-surgical recovery ( Xiong et al, 2020 ). During surgery, anaesthesia and operation might aggravate diabetic patients' symptoms.…”
Section: Introductionmentioning
confidence: 99%